Organization of import purchases of materials and equipment at machine-building enterprises on the example of MOTOR SICH - Kulyk, Polina; Нurzhii Natalia (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is to study the formation of the optimal organizational process of the import operations conduction. Design/methodology/approach. The basic principles of the research are historical, systemic and comparative. Also system-functional and structural-functional approaches are applied. Findings. The subject of research is theoretical, methodological and applied aspects of the formation and conduction of import purchases of raw materials and equipment. The relevance of the issue being under study is determined by the necessity of the modernization of emplementation of new modern ways of organization of import purchases at machine building enterprises. Enterprises of Ukrainian engineering sector take leading positions in the national and foreign markets. Therefore, the study of theoretical issues and practical research of he sphere of foreign economic activity are especially important for the formation of competitive advantages of machine-building enterprises. The reason of this importance is explaind with the fact that the organization of import purchases has undergone significant changes, connected with country’s economy market changes, which have led to the increase of this sphere. Research limitations/implications. The scientific significance of the work is that it gives the study of the process of import operations, the specifics of the engineering industry, the specifics of a foreign trade transaction and the description of main problems that machine-building enterprises face in the process of importing. Originality/value. In practice, the proper organization of import operations will contribute to the optimal functioning of purchase processes and the establishment of stable relations with suppliers of raw materials and equipment. It will also minimize the cost of materials supplied and speed up their delivery time.